ANALISIS KAUSALITAS ANTARA BI RATE DENGAN JUMLAH UANG BEREDAR DI INDONESIA - Maria Alvyonita Alvyonita; Paidi Hidayat (Ekonomi dan Keuangan, 2014)
This research has a purpose to analyze causality relationship between BI Rate and money supply (M1) in Indonesian. This research used time series data is monthly data period 2010-2012. The method of this research is method Cointegration test, Granger Causality test, and VAR. The results of analysis Cointegration test with VAR model, which means not a proper balance in the long run between BI Rate and M1. Granger Causality test analysis results, indicates that there is a bilateral causality relationship, are the BI Rate affect M1, and M1 affect BI Rate too.Keywords : BI Rate, Money Supply (M1), Cointegration test, VAR, and Granger Causality test